Inaugural Issue, Crawling Now but Aimed at Running the Fastest - Satish Prasad Barnawal (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2014)
Human immunodeficiency virus (HIV) causing Acquired immunodeficiency syndrome (AIDS) is a major public health problem [1]. The rapid extension of HIV is a global health challenge that has both social and economic implications [2]. Currently there are 40 million individuals infected with the HIV globally [3]. Nearly 95% of the infected ones are unaware of their HIV or AIDS status [4]. Central Asia is a region of concern for expanding HIV epidemics [5]. South Asia is currently home to >2.5 million HIV infected individuals [6]. Such an enormous number of people with the infection necessitate proper address. The Journal of HIV for Clinical and Scientific Research, being operated from India, is an attempt to report updates of researches across the world to this part of the earth and vice versa.